A Brief History of Khubilai Khan - Clements, Jonathan, 1971- (London Philadelphia Running Press, 2010)
Relates the life of the Mongol leader and emperor of China who ruled at the time of Marco Polo, and describes how the grandson of Genghis Khan helped change nomadic warriors into rulers of a sedentary empire.
Include Notes and Index
Keywords: Mongols--Kings and rulers -- Kublai Khan, 1216-1294 -- China